The treatment of proximal humeral fractures with a “Polarus” intramedullary nail - Dall'Oca, C.; Maluta, T.; Leone, N.; Micheloni, G. M.; Lavini, F. (Acta Biomedica Atenei Parmensis, 2014)
Proximal humeral fractures are complex lesions with difficult management problems; therefore, they pose a challenge for orthopaedic surgeons. In the literature, numerous treatment techniques have been proposed for these kinds of fractures. In our study we reviewed 30 patients with a mean age of 75 years presenting a proximal humeral fracture (Neer 2-3) and treated at our clinic with a Polarus nail, with a mean follow-up of 7 years. We obtained 73.3% of good and excellent results in line with literature. Complications were recorded in 6 of the patients (20%) recruited in our study. In particular, 3 cases of proximal screw pull-out, 1 case of deep infection and 2 cases of acromio-clavicular joint impingement syndrome. The aim of our study was to review our case histories and compare them with the literature analysing this complex type fracture and treatment options.